The use of ICTs in the English class: an enriching experience - Cuestas, Anahí Diana (2012)
Globalization has caused significant changes all over the world in different fields. Education has been particularly affected by this process of transformation, especially due to the development and fast spread of the new information and communication technologies (NICTs) which have led to a paradigm shift in the teaching-learning process. The implementation of such technologies in and outside the classroom has fostered autonomous learning thus encouraging students to become more independent and more responsible for their learning processes in new educational environments. The aim of this paper is to describe an experience using different ICTs in an ESP class and to analyse the advantages and drawbacks of using these tools in this particular context.